The Role of the Family Physician in Hospital Part 2: Use of Hospital Privileges - Johnston, M. A. (1980)
A questionnaire on the hospital involvement of family doctors was completed by the active staff members of the Department of Family Medicine at St. Joseph's Hospital, Hamilton, in April, 1977. This paper is the second of four; the first dealt with the study's conception, design and methodology. This paper deals with the reasons why family doctors attend hospital, what they do there, how much time they spend there, and the use of hospital privileges, both attending and procedural. A discussion of the study's implications for general understanding of the family doctor's role, and necessary education for this role, concludes this section. Subsequent sections will give more detailed results of the family doctor's involvement in obstetrics and lastly the attitudes of family doctors toward their hospital environment.